Comprehensive analysis of blade geometry effects on Savonius hydrokinetic turbine efficiency: Pathways to clean energy - Shanegowda T.G.; C.M. Shashikumar; Veershetty Gumtapure; Vasudeva Madav (Energy Conversion and Management: X)
The rising global demand for clean and renewable energy has intensified interest in hydrokinetic energy harvesting, with Savonius turbines gaining attention due to their simplicity and low cost. While numerous studies have focused on refining blade designs for wind turbines, limited research has been conducted on water turbines to identify the best design. This study investigates the effect of blade geometry on the efficiency of Savonius hydrokinetic turbines to identify the optimal configuration. Three new blade designs were tested, incorporating inner blades and varying blade numbers. These designs were experimentally evaluated to identify the optimal turbine configuration for maximum efficiency, and the findings were then validated through numerical studies. Rotational analysis was conducted to investigate torque variations across a full turbine rotation from 0° to 360°, and flow characteristic analysis was performed by utilizing pressure and contour plots at critical positions, including 0°, minimum torque coefficient (CT Min), and maximum torque coefficient (CT Max). Results indicate that the 2-blade Savonius turbine achieved the highest efficiency, with a maximum torque coefficient of 0.29 and a power coefficient of 0.22. It demonstrated 63.5 % greater power efficiency compared to the 3-Blade Savonius Turbine, 2.65 times greater than the Segmented Quarter Savonius Turbine, and 2.26 times greater than the Concentric Arc Savonius Turbine. These findings highlight the importance of blade geometry optimization in improving the performance of Savonius turbines for efficient hydrokinetic energy generation.